2019
DOI: 10.1016/j.energy.2019.05.055
|View full text |Cite
|
Sign up to set email alerts
|

Solar pyrolysis of cotton stalk in molten salt for bio-fuel production

Abstract: Solar pyrolysis of cotton stalk was carried out in a molten salt reactor heated by 4 kW solar simulator. The effects of pyrolysis temperature and mass ratio of molten salt to biomass on pyrolysis products properties were investigated. The use of molten salt as pyrolysis media increased gas yield. At 850 C, the gas yield (mainly of CO and H 2) continued to rise from 41.35 wt% to 82.57 wt% when mass ratio of molten salt to cotton stalk increased from 0 to 10. Pyrolysis in molten salt significantly decreased bio-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(17 citation statements)
references
References 50 publications
0
17
0
Order By: Relevance
“…It should be noted that the biomass could be well immersed and dispersed in the molten salt in our device when the ratio of molten salt to biomass reached 5, which can make full use of the catalytic performance of molten salt. Moreover, under the condition of ensuring that all salts can be fully melted, the pyrolysis temperature of 850 • C is selected based on our previous work to obtain higher quality pyrolysis products [14].…”
Section: Experimental Setup and Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…It should be noted that the biomass could be well immersed and dispersed in the molten salt in our device when the ratio of molten salt to biomass reached 5, which can make full use of the catalytic performance of molten salt. Moreover, under the condition of ensuring that all salts can be fully melted, the pyrolysis temperature of 850 • C is selected based on our previous work to obtain higher quality pyrolysis products [14].…”
Section: Experimental Setup and Proceduresmentioning
confidence: 99%
“…Thus, the selectivity of molten salt to biomass pyrolysis products is the decisive factor to evaluate molten salts. The upgrading effect on different pyrolysis products of ternary carbonate have been widely reported [13][14][15]. Adinberg et al [4] observed the enhancement of the selectivity regarding the gas product with the molten Na 2 CO 3 -K 2 CO 3 during the fast pyrolysis of cellulose particles.…”
Section: Introductionmentioning
confidence: 99%
“…Figure 4 depicts the FT-IR spectroscopy curves of SMS-CSP, 70% PEG/SMS-CSP, and PEG. The peak at 1618 cm −1 was attributed to the stretching vibration of –OH 24 . The absorption peak at 3415 cm −1 was attributed to the stretching vibration peak of –OH 19 .…”
Section: Resultsmentioning
confidence: 99%
“…37 The effect of pyrolysis temperature on PC mass yield was similar to the effect on other biomass (e.g., cotton stalk, eucalyptus, and rice husk). [38][39][40] 3.2.2 Biochar 3.2.2.1 Physicochemical properties of biochar. Physicochemical properties for biochar are listed in Table 1.…”
Section: Thermogravimetric Analysis Of Pc Pc Cellulose and Pc Ligninmentioning
confidence: 99%